Large-area atomic layers of the charge-density-wave conductor TiSe2 - Wang, Hong (2020)
Layered transition metal (Ti, Ta, Nb, etc.) dichalcogenides are important prototypes for the study of the collective charge density wave (CDW). Reducing the system dimensionality is expected to lead to novel properties, as exemplified by the discovery of enhanced CDW order in ultrathin TiSe2 . However, the syntheses of monolayer and large-area 2D CDW conductors can currently only be achieved by molecular beam epitaxy under ultrahigh vacuum. This study reports the growth of monolayer crystals and up to 5 × 105 µm2 large films of the typical 2D CDW conductor-TiSe2 -by ambient-pressure chemical vapor deposition. Atomic resolution scanning transmission electron microscopy indicates the as-grown samples are highly crystalline 1T-phase TiSe2 . Variable-temperature Raman spectroscopy shows a CDW phase transition temperature of 212.5 K in few layer TiSe2 , indicative of high crystal quality. This work not only allows the exploration of many-body state of TiSe2 in 2D limit but also offers the possibility of utilizing large-area TiSe2 in ultrathin electronic devices.